Ефект взаємодiї (Реалії історичного партнерства академічних установ України і Росії) - Онопрієнко, В.І. (Видавничий дім "Академперіодика" НАН України, 2008)
У статті з’ясовано функції академічної науки і реалії їх здійснення в різні історичні періоди, проведено історичну реконструкцію форм взаємодії академій наук України і Росії, оцінено внески українських учених у
розвиток фундаментальних наук у Росії і російських учених у становлення й розвиток академічної науки України, створення нових наукових установ. Проаналізовано принципи і чинники ефективного партнерства академій наук України і Росії в умовах глобалiзації в контексті завдань входження в європейський і
світовий науковий простір та інноваційного перетворення економіки. The article defines the functions of academic science and reality of their implementation during various historical
epochs. Historical reconstruction of cooperation forms of Ukrainian and Russian academies of science is carried out.
Contribution of Ukrainian scientists to development of basic sciences in Russia as well as contribution of Russian
scientists to formation and development of basic science in Ukraine, foundation of new scientific institutions has been
evaluated. Principles and factors of efficient partnership of Ukrainian and Russian academies of science under
conditions of globalization are discussed in the light of objectives for entry into European and World scientific space and innovational transformation of economy.